PENGARUH GAME EDUKASI MATH BINGO PADA MATERI PERKALIAN SISWA KELAS V SD NEGERI 02 PAYARAMAN - Yuniar Tati; Jayanti; Ida Suryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the math bingo educational game on themultiplication material of grade V students of SD Negeri 02 Payaraman. This studywas conducted using a quantitative experimental method, the research designused was a quasi-experiment in the form of a nonequivalent control group design.The test consisted of 10 essay questions. The population of this study was allgrade V students of SD Negeri 02 Payaraman. The sample in this study was classV.A as the experimental class and class V.B as the control class. The sample inthis study used a purposive sampling technique. Data collection techniques usedwere observation, test methods, and documentation. Data analysis used normalitytests, homogeneity tests, and hypothesis tests. The software used is SPSS 26.From the results of the data processing, the researcher obtained a sig value (2-tailed) = 0.000 < 0.05, and a calculated t value = 4.354 > t table = 1.683. Inaccordance with the requirements of the hypothesis test, Ho is rejected and Ha isaccepted. This shows that there is an influence of the math bingo educationalgame on the multiplication material of grade V students of SD Nelgelri 02Payaraman.